Effects of frutalin and doxorubicin on growth, ultrastructure and gene expression in goat secondary follicles cultured in vitro. (October 2018) - Soares-Costa, M.A.A.; Costa, J.J.N.; Silva, A.W.B.; Cunha, E.V.; Paulino, L.R.F.M.; Silva, B.R.; Silva, A.L.C.; van den Hurk, R.; Silva, J.R.V.
Abstract: This study evaluated the effects of frutalin (0.6, 6.0 or 60.0 μg/mL) and doxorubicin (0.3 μg/mL) on survival, growth and ultrastructure of in-vitro cultured goat secondary follicles. The effects of these substances on the levels of mRNA for Casp3, Casp6, Bax, and Bcl2 were also investigated. Results showed that, after 6 days of culture, frutalin or doxorubicin reduced the percentage of normal follicles (P < 0.05), but doxorubicin had higher toxicity than frutalin. Except for follicles cultured with 0.6 μg/mL frutalin, follicular growth rate was reduced after culture with doxorubicin or frutalin (P < 0.05). The presence doxorubicin or 60.0 μg/mL frutalin increased the levels of mRNA for Casp3, Casp6, Bax, and Bcl2 (P < 0.05). Higher mRNA levels for Casp3, Casp6 and Bax were found in follicles cultured with doxorubicin, but higher levels of Bcl2 mRNA were found in follicles cultured with frutalin (P < 0.05). In conclusion, frutalin has lower toxic effects than doxorubicin on secondary follicles cultured in vitro . Highlights: Follicular growth rate is reduced after culture in vitro with doxorubicin or frutalin. Frutalin has lower toxic effects than doxorubicin on secondary follicles cultured in vitro. Doxorubicin and frutalin increases the levels of RNAm for Casp3, Casp6, Bax, and Bcl2.